Analysis of Large Scale Distributed Generation on Radial Distribution System: Case Study in Sri Lanka - Sivagnanam, M.; Selvanayagam, S.; Thiruvaran, T.; Vinothine, S.; Nandasiri, N.; Aravinthan, V. (IEEE, 2019)
Large-scale penetration of distributed resources is becoming a reality in many parts of the world. Large scale renewable distributed generation has challenges at the distribution level and significant work is done to optimize the generation to ensure improved grid functionality. This work focuses on analyzing the protection and reliability of large-scale penetration of solar PV system in lightly loaded distribution feeders. This work considers an actual feeder in Vavuniya, Sri Lanka with 10 MW solar plant. To identify the impacts to the distribution system, fault study was carried with back-feeding to the grid and impact on system reliability was evaluated using expected energy not-served. A solution based on the placement of reclosers, circuit breakers and fuses is proposed in this work.
Keywords: Distributed generation; large scale DR